Methodology to evaluate the behavior of water treatment sludge and other pasty waste as sustainable geomaterial: rheological and geotechnical approaches. - Tsugawa, Juliana Keiko (2022)
Beneficial reuse of drinking water treatment sludge (WTS) as geotechnical material may be an essential strategy to reduce the environmental impacts due to improper disposal of WTS into rivers, landfills, or sewage treatment plants. An important shortcoming of investigations on WTS reuse refers to representative samples since its characteristics present high variability (seasonally and spatially). To transform a pasty or very humid waste into a geomaterial is necessary to reduce water content by drying or introducing additives. During this process, the WTS characteristics change from liquid to solid. Methods and devices are applied to investigate the WTS in each consistency realm; however, none was adequate to determine the minimum additive content at plastic to semi-solid transition. This research presents a sampling methodology for pasty waste based on the Theory of Sampling, proposes a methodology integrating geotechnical and rheological concepts to characterize and analyze the WTS behavior from liquid to semi-solid states, and suggests an expedite method to determine the minimum additive content, which turns WTS into a workable material directly after mixing (without curing or drying), based on compaction criteria (MAC3). Also, the leachability of metals from WTS and WTS-additive mixtures were assessed by batch and column tests. Results indicated that the proposed sampling methodology reduces the variability of results and ensures a more trustworthy evaluation of parameters. The rheological approach can reinforce the traditional geotechnical tests used to characterize WTS and other pasty materials, and it is important to simulate real conditions of WTS reuse (transportation, spreading, pumping, mixing, etc.). The MAC3 procedure is easy, low-cost, and accurately determined the minimum additive content: 350% of lime and 1350% of rock powder, which was validated by unconfined compression tests (both mixtures reached su of 20 kPa: minimum su required to ensure spreading and workability). The WTS and WTS-rock powder are classified as non-hazardous and non-inert, while the WTS-lime is non-hazardous and inert. In conclusion, WTS-additive mixtures with lime and rock powder can be applied as daily covers for sanitary landfills or other applications with low solicitations.